Iceland’s Neighbours in the EU Entry Queue: Contrasts or Parallels in EU Enlargement to the North and the South-East - Bailes, Alyson J.K.; Þórdísardóttir, Jóhanna María (Stjórnsýslustofnun, 2009)
In 2009, Iceland finds itself negotiating for EU entry alongside a group of 7 candidates and potential candidates from the Western Balkans. All are much poorer than Iceland and suffer from the legacies of regional conflict, ethnic division and under-development, plus specific weaknesses of governance, law and order. However, all the Balkan applicants have a clear majority of public opinion in favour of the EU and (except for Serbia) a cross-party consensus on accession. The severity of their problems makes EU and NATO membership their only hope and chance of a peaceful future, and also provides the main motive for the EU to grant their wish. Indeed the EU practises a policy of ‘conditionality’, using the lure of accession as leverage to make them improve their ways. Iceland does not have the same life-and-death importance for the EU unless, eventually, in the context of Arctic strategy. Several EU states have made clear they would not wish Iceland to ‘jump the queue’ past the other candidates. There may be lessons here for Iceland’s handling of its own negotiations.